2008
DOI: 10.1002/dvdy.21703
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic GATA6 expression in primitive endoderm formation and maturation in early mouse embryogenesis

Abstract: The derivation of the primitive endoderm layer from the pluripotent cells of the inner cell mass is one of the earliest differentiation and morphogenic events in embryonic development. GATA4 and GATA6 are the key transcription factors in the formation of extraembryonic endoderms, but their specific contribution to the derivation of each endoderm lineage needs clarification. We further analyzed the dynamic expression and mutant phenotypes of GATA6 in early mouse embryos. GATA6 and GATA4 are both expressed in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 25 publications
3
97
0
1
Order By: Relevance
“…S4A, B), we assessed other Fgf ligands to identify which one may cause the increased phosphorylation of Fgfr2 in parthenotes. It was shown that Fgf3 and Gata4/6 were co-expressed in the parietal endoderm of post-implantation embryos (Shimosato et al, 2007;Cai et al, 2008;Pilon et al, 2008). Hence we analyzed Fgf3 immunostaining and found that, in contrast to control embryos, which revealed only background levels of Fgf3, parthenotes showed strong Fgf3-positive signals throughout all plasma membranes of both morulae and blastocysts (Fig.…”
Section: Developmental Dynamicsmentioning
confidence: 89%
See 3 more Smart Citations
“…S4A, B), we assessed other Fgf ligands to identify which one may cause the increased phosphorylation of Fgfr2 in parthenotes. It was shown that Fgf3 and Gata4/6 were co-expressed in the parietal endoderm of post-implantation embryos (Shimosato et al, 2007;Cai et al, 2008;Pilon et al, 2008). Hence we analyzed Fgf3 immunostaining and found that, in contrast to control embryos, which revealed only background levels of Fgf3, parthenotes showed strong Fgf3-positive signals throughout all plasma membranes of both morulae and blastocysts (Fig.…”
Section: Developmental Dynamicsmentioning
confidence: 89%
“…All of the aforementioned genes are pivotal factors regulating lineage segregation and cell fate determination (Russ et al, 2000;Strumpf et al, 2005;Shimosato et al, 2007;Cai et al, 2008). Similar to Tbr2(Eomes) homozygous mutants, most parthenote embryos demonstrated a lack of diploid dividing trophoblast cells, impaired or retarded development of the neuroectoderm and brain, and multiple mesodermal defects (Sturm et al, 1994;Bulfone et al, 1999;Russ et al, 2000;Kwon and Hadjantonakis, 2007).…”
Section: Developmental Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…L'invalidation génique de Gata6 entraîne, quant à elle, une absence d'épithélium d'EPr à E4,5 indiquant que Gata6 est requis pour sa mise en place [9]. Néanmoins, ces analyses, pour être plus précises, nécessitaient une étude des phénotypes aux stades plus précoces, avant 4,5 jours après la fécon-dation.…”
Section: Revuesunclassified